A major review of stakeholder perspectives on the purposes of primary physical education. (May 2020) - Ní Chróinín, Déirdre; Fletcher, Tim; Jess, Mike; Corr, Méabh
While there may be some broad agreement about the purposes of primary physical education, there is dramatic variance in how these purposes are prioritised and enacted. Primary physical education consequently focusses on multiple, often competing, priorities. To gain a better understanding of this issue we review how different stakeholders view the purposes of primary physical education. We analysed 95 qualitative studies published between 2000 and 2017 that focussed on the views of different stakeholders. Across all stakeholders, the main purposes of primary physical education were identified as being physically active and learning physical, social, and emotional skills. Teachers and pupils were the most represented stakeholders, while the limited representation of school principals and policy makers was noted. The review indicates a need to examine the perspectives of those underrepresented stakeholders, serving as an entry point for bridge-building to shape the future direction of primary physical education.